Urinary schistosomiasis in school aged children of two rural endemic communities in Edo State, Nigeria - Rukeme M. Noriode; Emmanuel T. Idowu; Olubunmi A. Otubanjo; Margaret A. Mafe (Elsevier, 2018)
Background: Urinary schistosomiasis is endemic in many rural communities of Nigeria and school aged children are mostly affected. A cross-sectional study was carried out to assess the prevalence and intensity of urinary schistosomiasis infection among 251 school aged children in two communities of Ovia South West LGA of Edo State, Nigeria, as well as their knowledge on the control/elimination measures. Methods: Urine samples were collected and examined by microscopy using filtration technique. In addition, a questionnaire survey was conducted among school-aged children and health care providers, probing their knowledge, attitude and practices on on-going control activities. Results: The prevalence of urinary schistosomiasis among the school-aged children was 65.3%. The prevalence was generally higher among females (68.8%) and children in the age groups 10-14 (69.9%). The intensity of infection ranged from 1 to 5044 (mean = 449.8) eggs/10 ml of urine with a higher proportion having heavy infections (76.8%, P < 0.05). Water contact was attested by 123 (49.0%) of the children; of these 123, 74 (60.1%) were infected. The children's knowledge on urinary schistosomiasis was deficient. Conclusion: The high prevalences reported in these communities require integrated approach to control which essentially should incorporate the provision of safe water supply and sanitary facilities, and health education in addition to the annual mass praziquantel distribution, to reduce transmission. Keywords: Urinary schistosomiasis, Prevalence, Intensity, School aged children, Rural communities